Developmental pharmacokinetics of propylene glycol in preterm and term neonates. (14th December 2012) - De Cock, Roosmarijn F. W.; Knibbe, Catherijne A. J.; Kulo, Aida; de Hoon, Jan; Verbesselt, Rene; Danhof, Meindert; Allegaert, Karel
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT Propylene glycol is commonly used as an excipient in dose forms and is ingested by neonates when administering different drugs. While propylene glycol is generally considered to be safe, toxic effects like bradycardia, lactic acidosis and convulsions have been reported. Information on the pharmacokinetics of propylene glycol in neonates is lacking to provide insight into the possible risk of toxicity. WHAT THIS STUDY ADDS This study describes the pharmacokinetics of propylene glycol in preterm and term neonates co‐administered with paracetamol and phenobarbital. A pharmacokinetic model was developed which identified birth weight and postnatal age as important covariates for clearance. The model was used to simulate exposure to propylene glycol co‐administered with both drugs. AIM Propylene glycol (PG) is often applied as an excipient in drug formulations. As these formulations may also be used in neonates, the aim of this study was to characterize the pharmacokinetics of propylene glycol, co‐administered intravenously with paracetamol (800 mg PG/1000 mg paracetamol) or phenobarbital (700 mg PG/200 mg phenobarbital) in preterm and term neonates. METHODS A population pharmacokinetic analysis was performed based on 372 PG plasma concentrations from 62 (pre)term neonates (birth weight (bBW) 630–3980 g, postnatal age (PNA) 1–30 days) using NONMEM 6.2. The model was subsequently used to simulate PG exposure upon administration of paracetamol or phenobarbital in neonates (gestational age 24–40 weeks). RESULTS In a one compartment model, birth weight and PNA were both identified as covariates for PG clearance using an allometric function (CLi= 0.0849 × {(bBW/2720)1.69× (PNA/3)0.201}). Volume of distribution scaled allometrically with current bodyweight (Vi= 0.967 × {(BW/2720)1.45}) and was estimated 1.77 times higher when co‐administered with phenobarbital compared with paracetamol. By introducing these covariates a large part of the interindividual variability on clearance (65%) as well as on volume of distribution (53%) was explained. The final model shows that for commonly used dosing regimens, the population mean PG peak and trough concentrations range between 33–144 and 28–218 mg l−1 (peak) and 19–109 and 6–112 mg l−1 (trough) for paracetamol and phenobarbital formulations, respectively, depending on birth weight and age of the neonates. CONCLUSION A pharmacokinetic model was developed for PG co‐administered with paracetamol or phenobarbital in neonates. As such, large variability in PG exposure may be expected in neonates which is dependent on birth weight and PNA.